Answer:
a
Step-by-step explanation:
51edf + (5) is 100 so its 300
On the x column, you would write 1, 2, 3, 4, and so on. Then, in the y box, you plug in that number into the equation. Write your answer in the y column.
For example, if x = 1, then 1^2 + 2 - 8 = - 5.
If x = 1, y= -5
Answer:

Step-by-step explanation:
10 * sqrt(81/25 * -1) = 10 sqrt(81/25) * sqrt(-1) = 10 *9/5 * i
You could simplify this work by factoring "3" out of all four terms, as follows:
3(x^2 + 2x - 3) =3(0) = 0
Hold the 3 for later re-insertion. Focus on "completing the square" of x^2 + 2x - 3.
1. Take the coefficient (2) of x and halve it: 2 divided by 2 is 1
2. Square this result: 1^2 = 1
3. Add this result (1) to x^2 + 2x, holding the "-3" for later:
x^2 +2x
4 Subtract (1) from x^2 + 2x + 1: x^2 + 2x + 1 -3 -1 = 0,
or x^2 + 2x + 1 - 4 = 0
5. Simplify, remembering that x^2 + 2x + 1 is a perfect square:
(x+1)^2 - 4 = 0
We have "completed the square." We can stop here. or, we could solve for x: one way would be to factor the left side:
[(x+1)-2][(x+1)+2]=0 The solutions would then be:
x+1-2=0=> x-1=0, or x=1, and
x+1 +2 = 0 => x+3=0, or x=-3. (you were not asked to do this).
Answer:
y=20-3x
Step-by-step explanation: